성장기 비글에서 두개골에 가한 외력이 두개안면골 성장에 미치는 영향 - 임효섭 (The Graduate School, Ajou University, 2005)
In most of the cases, deformational plagiocephaly may be followed by facial deformation, and it takes a lot of risk in treating the cranial deformation surgically. If it is possible to remodel craniofacial appearance nonsurgically before the growth of craniofacial bone is completed, additional corrective surgery which can be hazard to patients may not be needed. Craniofacial bone is formed by the process of resorption and deposition of bones which are related to volume expansion of the brain parenchyma. By the process of bone resorption and deposition, the shape of cranial bone and skull base is formed and consequently, the skull base affects the shape of facial bone. When external force is applied to the cranial bone in the growth period, there will be three changes in sequence. First, the shape of the cranial bone will be changed and then volume expansion of brain will induce even more change in the shape of skull base. Finally facial bone also can be affected. In this hypothesis, we have done experimental study using growing Beagles and review of documents. Specially designed helmets were put on nine Beagles from the third to the ninth week of postnatal period and external force was applied to temporoparietal area. After the growth was completed, skeletonization was done and we measured the length, width and height of entire craniofacial, cranial, maxillary bone and mandible by using caliper. We then analyzed this data in comparison with three Beagles of normal control group. Statistics were done by independent T-test and Pearson correlation, using SPSS version 10.1. Because there was size difference in each Beagle, we used ratio of width and height to anteroposterior diameter as experimental data. As a result, the ratio of width to length of entire craniofacial, cranial and maxillary bone was significantly low compared to control group. However, there was no significant difference in the ratio of width to length of mandible and height to length of entire craniofacial, cranial and maxillary bone. In the group with significant difference, the relationship among craniofacial, cranial and maxillary width had strong correlation. The relapse was not found after taking off Beagles' helmets until the growth was completed. In the growth period of craniofacial bone, external force affected change in the shape of cranial and maxillary bone. Even when external force was no more applied, it did not relapse. Therefore, we can admit that change of cranial bone induces change of facial bone. We hopefully believe that it will be useful to apply this concept to patients with skull deformity and deformational plagiocephaly.
학위논문(석사)--아주대학교 대학원 :의학과,2005